Composition and species richness of flagellate protozoa from environments associated to the Baía river (Mato Grosso do Sul State, Brazil): influence of the hydrological period and the connectivity - doi: 10.4025/actascibiolsci.v32i4.6307 - Janielly Carvalho Camargo; Luiz Felipe Machado Velho (Acta Scientiarum. Biological Sciences, 2010)
Despite flagellate protozoa are important for the metabolism of aquatic ecosystems, researches about the ecology of this community is scarce. Therefore, this study investigated the influence of flood regime and hydrological connectivity on the patterns of composition and species richness of protozoan flagellates from aquatic environments in the upper Paraná river floodplain. To this end, samplings were undertaken in two periods of the hydrological cycle (March 2008 and September 2008), at six lentic environments associated with the Baía river (three are connected to the river, and three are isolated). 120 taxa were identified in the studied area, distributed in 10 orders and one residual group. This high species richness was sustained by the order Euglenida, which contributed with 70% of total species. The species composition was significantly different between periods and environments, as well as species richness, which was higher in connected environments during the high water period. The results evidenced that the flood pulse and hydrological connectivity are relevant factors driving the structure and dynamic of plankton flagellate protozoa community in the upper Paraná river floodplain.